Quantitative Determination of Surface Morphology of Red Blood Cell - Özlem Kocahan Yılmaz (Journal of Advanced Research in Natural and Applied Sciences)
In this study, the determination of the surface morphology of red blood cell (RBC) from interferogram image obtained by quantitative phase imaging (QPI) method is presented. QPI, is an optical measurement method frequently used in recent years, allows to obtain quantitative data for different samples (cell, thin film surface, etc.). Many measurement setups at the micrometer level and with nanometer precision have been designed for quantitative surface determination. Among these, white light diffraction phase microscopy (WDPM) is a design that combines the advantages of off-axis holography-specific speed and phase sensitivity associated with common path interferometry. Interferogram image of RBCs have been formed by the WDPM setup. Analysis of this image has been carried out by Fourier transform. As a result of this analysis, three-dimensional (3D), dynamic (observable from all angles) and height-known profiles of RBCs have been created. From the height profiles, the parameters related to the morphology of RBCs as the projected surface area (PSA), diameter (D), mean corpuscular volume (MCV) and total surface area occupied by the cell (SA), have been determined quantitatively. In addition, two-dimensional images,obtained by examining blood samples with light microscopy and scanning electron microscopy (SEM), have been compared with the data achieved by WDPM. The advantages and disadvantages of WDPM and light microscopy and SEM, which are commonly used in biomedical measurements, are discussed through the results. In this way, it was possible to see the difference between QPI and traditional methods used to imaging the cell surface.